Pengaruh Flash Sale, Live Streaming, Dan Hedonic Shopping Motivation Terhadap Impulse Buying Pengguna Shopee (Studi Kasus Mahasiswa Universitas Islam Malang) - Neni, Neni; Basalamah, Muhammad Ridwan; Wahyuningtyas, Nanik (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research investigates the effects of Flash Sale, Live Streaming, and Hedonic Shopping Motivation on impulse buying behavior among Shopee users, specifically focusing on students from an Islamic University. The study employs a quantitative approach, utilizing a Ferdinand formula with a sample of 85 respondents. Data analysis was conducted using SPSS, covering tests for normality, classical assumptions, hypothesis testing, multiple linear regression, and the adjusted R² coefficient. The findings indicate that Flash Sale does not affect impulse buying, while Live Streaming and Hedonic Shopping Motivation both have a significant impact on impulse buying. Keywords: Flash Sale, Live Streaming, Hedonic Shopping Motivation, Impulse Buying